Предмет:
МатематикаАвтор:
анонимСначала сократим данное выражение:
(а2 + (4 * в2)/(2 * в) + (2 * a)/а/(2 * в) + 1)/а + (2 * в)/в = (а2 + (4 * в2)/(2 * в) + (2 * a * 2 * в)/а + 1)/а + (2 * в)/в = (а2 + (4 * в2)/(2 * в) + (4 * a * в)/а + 1)/а + (2 * в)/в = (а2 + (2 * в) + (4 * в) + 1)/а + (2 * в)/в = а2/а + (2 * в)/а + (4 * в)/а + 1/а + 2 = а + (6 * в)/а + 1/а + 2.
Подставляем значения:
-2 + (6 * 3,5)/(-2) + 1/(-2) + 2 = -2 - (3 * 3,5) - 0,5 + 2 = -2 - 10,5 - 0,5 + 2 = -11.
Автор:
mauricioДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть